Selective Enhancement of Photoresponse with Ferroelectric‐Controlled BP/In2Se3 vdW Heterojunction - Jian Wang; Changlong Liu; Libo Zhang; Jin Chen; Jian Chen; Feilong Yu; Zengyue Zhao; Weiwei Tang; Xin Li; Shi Zhang; Guanhai Li; Lin Wang; et al. (Advanced Science, 2023)
Abstract Owing to the large built‐in field for efficient charge separation, heterostructures facilitate the simultaneous realization of a low dark current and high photocurrent. The lack of an efficient approach to engineer the depletion region formed across the interfaces of heterojunctions owing to doping differences hinders the realization of high‐performance van der Waals (vdW) photodetectors. This study proposes a ferroelectric‐controlling van der Waals photodetector with vertically stacked two‐dimensional (2D) black phosphorus (BP)/indium selenide (In2Se3) to realize high‐sensitivity photodetection. The depletion region can be reconstructed by tuning the polarization states generated from the ferroelectric In2Se3 layers. Further, the energy bands at the heterojunction interfaces can be aligned and flexibly engineered using ferroelectric field control. Fast response, self‐driven photodetection, and three‐orders‐of‐magnitude detection improvements are achieved in the switchable visible or near‐infrared operation bands. The results of the study are expected to aid in improving the photodetection performance of vdW optoelectronic devices.